The Role of Marriage Counseling Services in Efforts to Improve Household Harmony for Newly Married Couples (Case Study at Al-Amien Applied Psychology Institute Al-Amien Islamic Boarding School Prenduan Sumenep) - M. Farhan Yudhistihra MHS; Bagus Amirullah (Penerbit Hellow Pustaka, 2025)
Marital harmony is a condition where happiness is achieved, resulting in a complete, peaceful, and happy family. Marriage counseling services can help newlywed couples avoid conflicts and achieve harmony. This study uses a qualitative approach with data collection techniques including interviews, observation, and documentation. The results show that at the Al-Amien Applied Psychology Institute, marriage counseling consists of three stages. The initial stage is to build a relationship, investigate client complaints, and establish an agreement on the counseling process. The core stage involves providing advice to clients based on the established agreement. The final stage is when clients apply the advice given by the counselor. Additionally, eL-PsikA uses a Personal Approach method that is tailored to the client's condition to make it easily understood. The role of marriage counseling services in enhancing marital harmony at this institute technically includes a preventive function. This includes preparing newlywed couples to understand each other, listen to, and respect differences. The mental-spiritual preparation aims to help clients receive guidance from Allah SWT as a foundation to navigate life in a proper and good way.